Híbridos de milho para silagem em diferentes densidades populacionais na safra e safrinha - Severo, Igor Kieling (2021)
The objective was to evaluate the productive performance and qualitative aspects of the silage of corn hybrids cultivated in the harvest and off-season in different sowing densities. Two experimental tests were carried out. In the first trial, the productive aspects were evaluated, in which a randomized block design was used with four area replications, with treatments in a 3x4 factorial arrangement (three hybrids and four population densities), with the season (season and out of-season) used in statistical analysis as a repeated measure over time. In the second experimental trial, the qualitative aspects of the silage were evaluated using a completely randomized design, with treatments in a 3x4 factorial arrangement (three hybrids and four population densities) with five replications (experimental silos), using the season as a measure repeated in time. The plant populations evaluated were 60,000, 80,000, 100,000 and 120,000 plants ha-1. The evaluated hybrids were B2688, B2433 and B2410. The first sowing was carried out on October 9, 2019 (season) and the second sowing on February 19, 2020 (off-season), through the no-till system. The basic fertilization consisted of 670 kg ha-1 of NPK fertilizer in formulation 5-25-15. The cover fertilization was 140 kg ha-1 of N, performed in two applications, one at the V4 stage and the other at the V8 stage of the crop. In the first experiment, evaluations of initial and final plant stand, stem diameter, ear insertion height, plant height, dry matter content of the entire plant, production of green and dry matter, morphological separation (leaf, stem, cob, cob straw), yield components (grain weight, row per ear, grains per row and grains per ear) and score for late blight. In the second experiment, after 60 days of ensiling, evaluations of aerobic stability, pH, electrical conductivity, water activity, dry matter losses, neutral detergent fiber, acid detergent fiber and crude silage protein were carried out. The hybrid B2433 showed higher production of dry matter in relation to the hybrid B2410, with no difference for the other comparisons between these hybrids for this characteristic. Only water activity and electrical conductivity were altered by the corn hybrids, which were higher for the B2410 hybrid than the others, which did not differ from each other. The increase in plant density from 60 to 120 thousand plants ha-1 increased the production of silage dry matter. The electrical conductivity, as well as the neutral detergent and acidic fiber content of the silage, increased with the increase in the density of corn plants. The pH and aerobic stability of the silage were reduced with the increase in the density of corn plants per hectare. The crude protein content and dry matter losses showed quadratic variation with the increase in the density of corn plants, with the highest values observed for the populations of 80 and 100 thousand plants ha-1, respectively. The forage production, as well as the pH and electrical conductivity of the silage, was higher during the main crop period. The silage produced in the off-season showed the highest values of water, crude protein and fiber in acid detergent activity. The neutral detergent fiber content, dry matter losses and silage aerobic stability did not differ between maize sowing times. The increase in the sowing density and the use of more productive hybrids in the period of the main harvest are alternatives to increase the production of quality silage.